Makna Denotasi dan Konotasi pada Puisi “Iżā Gāmarta Fī Syarafin Marūmin” Karya Abu Toyyib Al-Mutanabbi - Thaariq, M. Ulfat; Mustari, Mustari (JURNAL Al-AZHAR INDONESIA SERI HUMANIORA, 2025)
This research aims to analyze the denotation and connotation meanings of poetry "Iżā Gāmarta Fī Syarafīn Marūminn" by Abu Toyyib Al-Mutanabbi using Roland Barthes'. This research to elucidate the denotation and connotation meanings inherent in each stanza of the poem, as well as to investigate the ideological values expressed, such as courage, honor, and sacrifice. The research method employed is a qualitative approach, data collection techniques through observation and documentation. The analysis of the poem text is conducted in-depth as the primary data, while related literature is treated as secondary data. This analysis is used to increase understanding of the sign system and meaning contained in poetry. The results of this study demonstrate that the denotation of the poetry depicts a life characterized by struggle, honor, and ambition, which serve as the primary objectives of existence. In contrast, the connotation of the poem represents the values of courage in the face of adversity, including physical and emotional sacrifice, and the pursuit of excellence through resilience. The poem reflects Arab cultural values that uphold courage, wisdom, honor as ideal human characters. Additionally, symbols such as stars and fire are utilized as a means of representing the struggle and purification of character.Keywords - Connotation Meaning, Denotation Meaning, Semiotics.